The capitalisation of Irish agriculture - Johnston, Joseph (Statistical and Social Inquiry Society of Ireland, 1942)
The value of a farm from a strictly agricultural point of view is a capitalisation of the income which a purchaser, whose principal occupation is farming, might hope to make in virtue of his ownership as such. In making his valuation the purchaser considers the farm as a whole? land, buildings, fences, situation, water supply, etc., as well as rates and annuity charges, and does not consciously assign a specific value, positive or negative, to each item. All the elements of value which analysis may distinguish are in fact inseparable parts of a common whole. Nevertheless for our purposes it is necessary to analyse and distinguish.
Read on Friday, 21th February, 1942
Keywords: Irish agriculture; Farm valuation; 314.15